Comparing the Diagnostic Accuracy of Direct Digital and Conventional Intraoral Peri-apical Radiographs in Identifying Interdental Bone Loss: An Observational Study - Chakraborty Sankha S; Manohar Balaji; Bhuyan Lipsa; Anupriya CH; Kaur Awneet (Wolters Kluwer Medknow Publications, 2024)
The evaluation of conventional two-dimensional radiography is crucial in making the diagnosis of periodontitis. Radio-visiography (RVG) is one of the digital imaging modalities that have received significant recognition as a replacement for film-based radiography due to its improved image quality, quick turnaround time, and minimal radiation dose. In order to compare the diagnostic efficacy of Direct Digital and Conventional Intraoral Peri-apical Radiographs in identifying Interdental Bone Loss, the present investigation was carried out. A cross-sectional observational study was conducted among 96 patients prospectively. Radiographs were exposed using a Gendex Oralix AC machine. Statistical data was analyzed using IBM SPSS statistical software using appropriate statistical tests. For both age categories, the radiographic method yielded a higher mean score than the periodontal probe method. The mean scores were noted to be higher following surgery. The radiographic approach recorded a greater mean score when gender groups were compared than the periodontal probe, which had a lower mean score. The mean scores after surgery were noted to be lower than the radiography approach and higher than the periodontal probe. The results demonstrate the radiographic technique's significant advantage over clinical tests in determining furcation regions as well as its superior accuracy in spotting periodontal disintegration over clinical probing.